ﻫندسة أصول الفقه: نحو مقاربة إندونيسية للاجتهاد - Nur, Iffatin; Ali, A. Muhdhor (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2022)
لقد دون علم أصول الفقه من قبل مذاهب شىت بما فيها من تعدد مناهج االجتهاد واالستنباط. كما شهدت القرون الوسطى تطورا هائال حيث ظهرت ونشأت فيها نظريات ومقاربات يف جمال استنباط األحاكم أصوال وفقها. غري أن هناك فجوتني إقليمية وزمانية بني إندونيسيا والقطر العريب الواقع فيه ذاك اتلطور، األمر اذلي يعرقل تطبيق األحاكم املستنبطة وعالجا للقضايا الفقهية بإندونيسيا من ًّ بشلك اكمل شامل. فانطالقا من هذا، احلاجة ماسة إىل صياغة مقاربة أرخبيلية حل خالل صياغة منهج جديد يسىم بدمج املصدرين أو يقال بادلمج بني املصدرين. ويتم تنفيذه عرب دمج مصدرين هما مصادر الترشيع اإلساليم والترشيع القانوين حفاظا ىلع االستقرار وصيانة للبالد عن االنهيار. بناء ىلع احلجة السابقة، استند هذا ابلحث ىلع دراسة استقصائية بتحليل املقارب الفقيه يف العرب واندونيسيا. من خالل ذلك املنهج، قصد ابلحث يلكشف موضوع الفقه العرب كمرجع يف صياغة الفقه بمنهج االجتمايع واثلقايف للمجتمع اإلندونييس. استنتج هذا ابلحث بأن ً بني مصادر الفقه اإلساليم ومصادر القانون الشعب اإلندونييس كجهد إلنشاء منتجات الفقهية اتلكيفية هناك تكامل يف إندونيسيا. The methods of ijtihâd and istinbâth have been adopted and practiced by all schools of thought of Islamic jurisprudence (madzhab fiqh). The Middle Ages witnessed a tremendous development in which theories and approaches emerged in the field of istinbâth al-ahkâm (deducing legal provisions) both in ushûl (principles) and fiqh (Islamic jurisprudence). However, there are two gaps, regional and temporal ones, between Indonesia and Arabian countries where that development took place. These have been impeding the application of those developed provisions fully and comprehensively. From this point of view, there is an urgent need to formulate an archipelagic (Nusantara, Ind.) approach to solve the issues of jurisprudence in Indonesia through the formulation of a new approach by integrating or merging 2 (two) legal sources. It is implemented through the integration of two sources, the Islamic and Indonesian legislation sources with the purposes of preserving the country’s stability and preventing it from its collapse. According to the above argumentation, this study is carried out through a literature review with an analytical study on the fiqh approach in Arab and Indonesia. This is then intended to conduct a study of fiqh in Arab countries as the reference to formulate fiqh with the sociocultural approach of the Indonesian society. The findings indicates that there is an integration between the source of Islamic law and the Indonesian law as an effort to build an adaptive product of fiqh in Indonesia.